Neonate with Microphthalmia, Cleft Lip and Palate, Omphalocele, Polydactyly, Atrial Septal Defect and Patent Ductus Arteriosus: A Likely Case of Patau Syndrome - Algutaini, Safana Abdullah; Sreiwy , Alaa Ammer (Journal of Medical Health Research and Psychiatry, 2025)
This report describes a one-day-old female neonate presenting with multiple congenital anomalies, including bilateral microphthalmia, cleft lip and palate, omphalocele, unilateral polydactyly, Atrial Septal Defect (ASD), and Patent Ductus Arteriosus (PDA). The omphalocele was surgically repaired shortly after birth. These features are characteristic of Patau syndrome (Trisomy 13), a rare chromosomal disorder caused by an extra copy of chromosome 13. Genetic testing is ongoing to confirm the diagnosis. This case underscores the importance of early recognition, multidisciplinary care, and family counseling for neonates with severe congenital malformations.